Pengaruh Penambahan Pasir Sungai Terhadap Permeabilitas Tanah Lempung - Gabriel Rasinan; Benyamin Tanan; Irwan Lie Keng Wong (Paulus Civil Engineering Journal, 2021)
This study aims to seek the effect of sand on clay soil permeability. Because the problem that often happened in road construction is the characteristics of clay that are unstable to be used as the basis for road construction. It can be damaged such as cracks, holes, and puddles. Therefore, there must be some solution to take to fix the seepage value. The research method used constant head to calculate the water flow through the soil sample in units of time that have been formulated in Darcy’s law. The experiment was tested in the Soil Mechanics Laboratory UKI Paulus Makassar with the soil samples from North Toraja and the sand from the Jenebarang River. The experiment result found that after adding 15% of sand from points 1, 2, and 3 have increased up the permeability value. After all, this study shows that the higher addition of sand, the higher the permeability.